Razvoj računalniškega treninga vidne pozornosti in preverjanje njegove učinkovitosti pri zdravih mladostnikih - Alič, Lea (Psihološka obzorja (Ljubljana), 2021)
Visual attention, an important cognitive function that helps select relevant information in the visual scene and filter out irrelevant information, can be trained and improved. We developed computer-based training of focused and distributed attention and of switching between global and local information processing and tested its effectiveness in healthy adolescents. In the experimental group (n = 11), training lasted 6 weeks, with three 20-min sessions per week. After each training session, participants received feedback on their performance and were able to track their progress. The control group (n = 10) received no intervention during this time. To test the effects of training, participants in both groups completed various cognitive tasks before and after training that shared features with the trained tasks to varying degrees. Compared to the control group, the experimental group showed greater improvements in reaction times on the selective attention and global-local processing tasks, while no consistent training effects were found on the other cognitive tests used. Thus, the results showed that the developed training can improve selected aspects of visual attention, but in line with most findings on cognitive training in the literature, the effect is limited to improved performance on tasks that are very similar to the trained tasks.
Keywords: cognitive ability; cognitive processes; cognitive psychology; cognitive training; emerging adulthood; executive function; inhibicija; inhibition; izvršilne funkcije; kognitivna psihologija; kognitivni procesi; kognitivni trening; preklapljanje; preklop v odraslost; spoznavne sposobnosti; task switching; The Simon task; The task switching paradigm